Direito à informação e os meios de Comunicação Social: uma análise a partir da jurisprudência dos tribunais de 2012 a 2017 - LIMA, Dandara Miranda Teixeira de (2018)
The right to information harbors publicity, transparency and the flow of information, enabling each individual to have access to various subjects and make their own judgments about them. On the other hand, the media is a natural instance of information activity with a high penetration power, which legitimized itself as a public interest service, but which encompasses diverse economic and political interests that challenge its social function and demand the protection of the right to information before the media action in order to safeguard the interest of society in its scope. In this sense, the general objective of the present investigation was to analyze how the right to information effectively applies to the media, based on the judgments of the Federal Supreme Court (STF), Superior Court of Justice (STJ) and the Court of Justice of Maranhão (TJMA), within the time span from 2012 to 2017, in order to understand the meanings attributed to this relationship by the Judiciary in the concrete cases submitted to it. To achieve this, we chose methodological procedures of bibliographic analysis, documentary analysis and content analysis of Laurence Bardin (1977). It was found that the right to information in relation to the media is recognized, but it lacks further discussion on its applicability, especially in the context of new information and communication technologies.